As contribuições das ciências cognitivas para ecolinguística - Albuquerque, Davi Borges de (2016)
This paper has as the main objective to list the contributions of Cognitive Sciences to Ecolinguistics, which is a recent approach to language studies. Thus, Ecolinguistics theoretical models that are related to cognitive aspects, such Ecosystemic Linguistics and Dialectical Linguistics, will be presented. It will also present the contributions of cognitive sciences’ second wave and third wave to these different Ecolinguistic theories. Furthermore, it intends to elaborated a proposal which aims to develop Ecosystemic Linguistic theory and to supply tools to analyze several linguistic data, approaching them as mental and ecological phenomena. Finally, a case study will be conducted applying the proposal presented in the paper.